COORDINATE SYSTEM USED IN GEODESY - Ibragimov Lazizbek ,; Yoqubov Azamat ,; Axmadov Azimjon ,; Tursunpo`latov Jasur , (TADQIQOTLAR.UZ, 2024)
Abstract: This article provides information about the coordinate system used in geodesy nowadays, and it explains their advantages and disadvantages, as well as how they are divided when used in practice. It gives information about various types of coordinates used in geodesy, such as geographic astronomical, rectilinear, zonal rectilinear, geodetic coordinates, polar coordinates, and other types of coordinates.